Upaya Bank Indonesia Menanggulangi Money Laundering Dalam Perbankan Online - Wamafma, Filep; Sasea, Enni Martha; Marlina, Andi (Universitas Semarang, 2022)
Money laundering is a crime that can result in significant losses for the state since it can impair the national economy or state finances through a variety of criminal behaviours, and it is also very harmful to community actions. This study intends to describe the government's efforts to combat money laundering in internet banking, specifically in the case of Bank Indonesia. This study uses normative legal research as an approach. The establishment of a Special Work Unit based on Bank Indonesia External Circular No. 11/31/DPNP of November 30, 2009, is the outcome of the implementation of the Money Laundering Law on the prevention of money laundering in the online banking system, according to the findings of the research. In addition, banks must also implement CDD and EDD policies. Customer Due Diligence (CDD) is a process by which the bank must identify, verify, and monitor transactions to ensure that they are in line with the customer's profile. Because there is a substantial danger of money laundering and terrorism funding in the bank's interaction with its customers, the bank must conduct an intensive CDD method called Enhanced Due Diligence (EDD). In the position as the executor of anti-tipping off, which means that in bank activities, especially in reporting suspicious financial transactions, the bank is obliged to keep the reporting information confidential to the customer concerned. An information management system that supports an effort to prevent money laundering crimes must be owned by banks to facilitate monitoring in order to analyze suspicious finances.Pencucian uang menjadi salah satu kejahatan yang dapat menimbulkan kerugian besar bagi negara karena dapat mengancam serta merugikan negara dengan meningkatnya berbagai tindakan ilegal, dan juga sangat merugikan masyarakat. Studi ini bertujuan untuk mendeskripsikan upaya pemerintah dalam hal ini adalah Bank Indonesia menanggulangi money laundering dalam perbankan online. Studi hukum normatif digunakan sebagai metode dalam studi ini. Berdasarkan studi yang telah dilakukan diperoleh hasil bahwa upaya Bank Indonesia terhadap penanggulangan tindak pidana money laundering dalam sistem perbankan online adalah dengan pembentukan suatu Unit Kerja Khusus berdasarkan Surat Edaran Ekstern Bank Indonesia No.11/31/DPNP tanggal 30 Nopember 2009. Selain itu bank juga harus menerapkan kebijakan CDD dan EDD. Customer Due Diligence (CDD) adalah proses dimana bank harus mengidentifikasi, memverifikasi, dan memantau transaksi untuk memastikan kesesuaiannya dengan profil nasabah. Karena adanya bahaya pencucian uang dan pendanaan terorisme yang cukup besar dalam interaksi bank dengan nasabahnya, bank harus melakukan metode CDD intensif yang disebut Enhanced Due Diligence (EDD). Dalam kedudukannya sebagai pelaksana anti tipping off, yang artinya dalam kegiatan bank khususnya dalam pelaporan transaksi keuangan mencurigakan, bank wajib merahasiakan keterangan pelaporan terhadap nasabah yang bersangkutan. Sistem manajemen informasi yang turut mendukung sebagai upaya penanggulangan tindak pidana pencucian uang harus dimiliki oleh perbankan sebagai sarana kemudahan dalam memantau dan menganalisis keuangan yang mancurigakan.